Study on mechanical and durability properties of ternary blended concrete. (2022) - Prasad, E.V.; Phani Manoj, A.V.; Surya Teja, U.
Abstract: The cement manufacturing unit is the prime source of environmental contamination as it intakes a large amount of energy in the generation and releases a lot of CO2, which contributes to global warming. To overcome this an attempt has been made to find a partial alternative to cement. First, the cement is partially replaced with fly ash (FA) and then cement is partially replaced by optimum fly ash and eggshell powder. This study focuses on the mechanical and durability characteristics of M60 grade concrete. A ternary mix with fly ash 20%, eggshell powder 10%, and cement 70% displayed high compressive strength.